Automation of Keithley 617 Programmable Electrometer System for Obtaining Current-Voltage Characteristics - Arif Surachman; A. Suhendi; M M Munir (Pusat Teknologi Instrumentasi dan Otomasi (PTIO) - Institut Teknologi Bandung, 2010)
The hardware and software of the Keithley 617 Programmable Electrometer System, which is used for electrical characterization of materials and devices, have been automated so that users can work under convenient environment. The main constraint in automation of the system was budget. It was decided that the PCL488 ISA card is reused. The computer supporting the ISA bus was Pentium II with 128 Megabytes of RAM and the best operating system for the Pentium II computer was Windows 98 SE. The software driver for the PCL488 card was also updated to be CEC488 v7, which is the latest version for Windows. Interactive software for measurement, processing and displaying data has been written by using the Borland Delphi version 6.0, which is a programming language with graphical-user interface capability. Therefore, users can operate the system conveniently. Keywords: Electrometer, Device, GPIB, I-V characteristic, Material, Programming